Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00467-008-0914-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of high-degree steroid dependency in pediatric idiopathic nephrotic syndrome

Abstract: Most patients with idiopathic nephrotic syndrome are steroid-responsive, but about 50% relapse and often become steroid-dependent and exposed to long-term steroid complications. The aim of this study was to determine predictive risk factors for steroid and/or cyclosporine A (CyA) dependence. In France, steroid responsiveness is defined as remission after 1 month of oral prednisone (60 mg/m(2) per day) and-in the case of persistent proteinuria on day 30-three methylprednisolone pulses (MPP; 1 g/1.73 m(2) on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 25 publications
(25 reference statements)
1
25
1
3
Order By: Relevance
“…There is equal gender distribution in the African-American child [12], in contrast to the previous data of male predominance in the Caucasian child with FSGS [1,2]. The current treatment of choice is to slow the rate of progression [51], by a combination of vitamin E [18], prednisone [1], angiotensin converting enzyme inhibitor or angiotensin receptor blocker [14]. In the non-responsive cases, the addition of cyclosporine is supported by results of controlled clinical trials [22].…”
Section: Fsgs Is An Important Component Of Mcns In Childhoodcontrasting
confidence: 41%
See 1 more Smart Citation
“…There is equal gender distribution in the African-American child [12], in contrast to the previous data of male predominance in the Caucasian child with FSGS [1,2]. The current treatment of choice is to slow the rate of progression [51], by a combination of vitamin E [18], prednisone [1], angiotensin converting enzyme inhibitor or angiotensin receptor blocker [14]. In the non-responsive cases, the addition of cyclosporine is supported by results of controlled clinical trials [22].…”
Section: Fsgs Is An Important Component Of Mcns In Childhoodcontrasting
confidence: 41%
“…The definition of what comprises a complete remission remains problematic; it is generally accepted that, if the child has not completely cleared the urine of protein for 3-5 consecutive days after four weeks of prednisone, remission is incomplete. Some authors consider that a patient with two or more relapses during steroid tapering or within a month thereafter constitutes steroid-dependency [14]. These patients are classified as frequent relapsing/steroid-dependent.…”
Section: Treatmentmentioning
confidence: 99%
“…We believe our practice of administering ivMP for 3-5 days following non-response to four weeks of oral prednisolone, which is similar to the policy adopted by a majority of French Paediatric Nephrologists [4,5], has a number of advantages. It will help achieve remission in those children who require a higher dose of steroid to enter remission and also in those where adherence with initial oral therapy has been poor.…”
Section: Discussionmentioning
confidence: 95%
“…While good data exist regarding long-term outcomes following the ISKDC and other standard oral prednisone and prednisolone regimens, there are currently little long-term outcome data following regimens where additional ivMP is administered. One recent French study has reported an increased prevalence of steroid dependency and requirement for ciclosporin in children administered three doses of ivMP following failure to respond to 30 days of oral prednisone compared with those who responded to this initial course of oral therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…3 The risks of a child developing frequent relapses or becoming steroid-dependent are increased with the number of relapses in the first 6 months after initial treatment, younger age at the initial episode, in boys, prolonged time to first remission, haematuria in first episode, shorter time to first relapse and infection at first relapse. [4][5][6][7][8][9] The most consistent indicator for a frequently relapsing course is early relapse after initial treatment. Studies have not assessed whether the other factors are independent risk factors for predicting frequent relapses or steroid dependence.…”
Section: How To Cite This Articlementioning
confidence: 99%